INVESTIGATING ISLAMIC BUSINESS ETHICS PRACTICE TOWARD MILLENNIAL MUSLIM GENERATION - Nurlaili; Muhammad Iqbal Fasa; Diana Ambarwati (Institut Agama Islam Agus Salim Metro Lampung, 2023)
Islamic business ethics has the most basic purpose of a business or business which is to benefit and take blessings from activities carried out by others who need it. This study aims to find out how the application of business ethics among the Muslim millennial generation is in accordance with business ethics in Islam. so that later, it is hoped that the results of this paper can be used as a working concept (framework) or model for other business actors. The research was conducted in the form of descriptive using literature study and research development from the results of research that had been done previously. The results show that business/business actors among the Muslim millennial generation of university alumni in Metro City have implemented Islamic business ethics. In running a business/business and activities, business people have understood and practiced the basic principles or values of Islam based on the Qur'an and Hadith. The application of business ethics in Islam includes several aspects, namely principles, prices, marketing (advertising/promotion), and production.